STOCK UNDERPRICING FACTORS AFFECT IN INDONESIA FIRM: EVIDENCE ON INITIAL PUBLIC OFFERING ON 2017-2021 - Rollis Ayu Ditasari; Sendy Dwi Haryanto (CAPITAL: Jurnal Ekonomi dan Manajemen, 2024)
Abstract: This research aims to analyze the influence of underwriter reputation, financial leverage, proceeds, and firm age on initial IPO returns. In this research, IPO objectives are categorized into company growth opportunities, debt repayment, and increasing investors' working capital. This research sample consists of companies listed on the Indonesia Stock Exchange during the 2017-2021 period. The analytical tool used in this research is SPSS 25. The research results show that financial leverage has a significant effect on the underpricing of initial shares, while the underwriter; Income and company age do not have a significant effect on Initial Share Underpricing. This research contributes to better understanding the dynamics that occur in the IPO market, that volatility and market dynamics cause changes in the company's position on the stock market. These results are expected to provide valuable insights for investors, policy makers and market players.